The moss family Rhachitheciaceae (Dicranales, Bryophyta) in Thailand - Chantanaorrapint, Sahut; Sevanakun, Nilobon; Suwanmala, Orawanya; Sukkharak, Phiangphak; Printarakul, Narin; He, Si (Phytotaxa, 2021)
A taxonomic study of the family Rhachitheciaceae in Thailand is presented based on newly collected materials from field surveys and herbarium specimens. Two species are recognized, including Hypnodontopsis spathulata and Rhachithecium perpusillum. Hypnodontopsis spathulata, previously known only from the type locality, is reported here as a new genus and species record for Thailand. A key to species, taxonomic descriptions and illustrations are provided. In addition, the lectotype of Zygodon perpusillus (=Rhachithecium perpusillum) is also designated here.